Optimasi waktu tunggu dengan simulasi sistem antrian pada gerai F&B - Sugioko, Andre; Hidayat, Trifenaus; Chabella, Cynthia; Wenlicia, Frisca; Khrisna Cahya Gulo, Gede; Hardianto, Gregorius; Jeremiah, Morris (Jurnal Teknik Industri dan Manajemen Rekayasa, 2024)
F&B outlet, located in Sumarecon Mall Serpong, has a problem with long customer waiting times. Based on the root cause analysis, the cause was found to be human and machine factors. This study aims to analyze the queuing system of the F&B outlet and provide suggestions for improvement based on root cause analysis using simulation. The simulation software used is Promodel Software. The research methodology will begin with the creation of a simulation model based on actual data after the initial model has been tested for verification and validation. The initial model will be compared with 3 proposed improvements, namely ergonomic proposals, machine proposals and combination proposals, using the ANOVA method, using the waiting time as a comparison variable. The results showed that the 3rd proposal was able to provide savings in customer waiting time in taking orders by 40%. This is because the order-making process is much faster due to the proposals in terms of ergonomics and tool replacement, so that it can speed up the work process.